Biocatalytic Asymmetric Construction of Secondary and Tertiary Fluorides from β‐Fluoro‐α‐Ketoacids. (24th March 2022) - Fang, Jason; Turner, Laura E.; Chang, Michelle C. Y.
Abstract: Fluorine is a critical element for the design of bioactive compounds, driving advances in selective and sustainable fluorination. However, stereogenic tertiary fluorides pose a synthetic challenge and are thus present in only a few approved drugs (fluticasone, solithromycin, and sofosbuvir). The aldol reaction of fluorinated donors provides an atom‐economical approach to asymmetric C−F motifs via C−C bond formation. We report that the type II pyruvate aldolase HpcH and engineered variants perform addition of β‐fluoro‐α‐ketoacids (including fluoropyruvate, β‐fluoro‐α‐ketobutyrate, and β‐fluoro‐α‐ketovalerate) to diverse aldehydes. The reactivity of HpcH towards these fluoro‐donors grants access to enantiopure secondary or tertiary fluorides. In addition to representing the first synthesis of tertiary fluorides via biocatalytic carboligation, the afforded products could improve the diversity of fluorinated building blocks and enable the synthesis of fluorinated drug analogs. Abstract : Biocatalytic asymmetric synthesis of secondary and tertiary fluorides is performed by the pyruvate aldolase HpcH and its engineered variants, utilizing β‐fluoro‐α‐ketoacids as non‐native donor substrates. Rationalization of beneficial mutations and optimization of reaction conditions allowed for the chemoenzymatic preparation of fluorinated synthons with relevance to bioactive natural products and pharmaceuticals.